Signal Sequence Mutations as Tools for the Characterization of LamB Folding Intermediates - Duguay, Amy Rizzitello (American Society for Microbiology, 2002)
lamBA23DA25Y and lamBA23YA25Y tether LamB to the inner membrane by blocking signal sequence processing. We isolated suppressors of lamBA23DA25Y and lamBA23YA25Y, all of which mapped within the LamB signal sequence. Most interesting were mutations that changed an amino acid with a strong positive charge to an amino acid with no charge. Further characterization of two such suppressors revealed that they produce functional LamB that is localized to the outer membrane with its entire signal sequence still attached. Biochemical analysis shows that mutant LamB monomer chases into an oligomeric species with properties different from those of wild-type LamB trimer. Because assembly of mutant LamB is slowed, these mutations provide useful tools for the characterization of LamB folding intermediates.